2016
DOI: 10.1111/jvh.12557
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Hepatitis E virus breaking through the blood–brain barrier and replicating in the central nervous system

Abstract: Neurologic dysfunctions such as Guillain-Barre' syndrome, encephalitis, meningitis and transverse myelitis occur frequently in patients with hepatitis E virus (HEV) infection, and this study was conducted to better characterize the role of HEV in the pathogenesis of neurologic disorders. Genotype 4 strain of swine HEV was used to inoculate Mongolian gerbils. Reverse transcription-nested polymerase chain reaction (RT-nPCR), ELISA, histopathology, ultrastructural pathology and enzyme immunohistochemistry method … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
53
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(61 citation statements)
references
References 38 publications
6
53
0
2
Order By: Relevance
“…Finally, HEV RNA was detected in the liver from seven to 42 days post infection, which is consistent with the last days of HEV RNA detection in the swine model [110], suggesting that HEV RNA replication in the Mongolian gerbil is similar to its replication in the swine model. Using this model, a study has also shown that swine HEV-4 is able to cross the blood–brain barrier and replicate in the brain and the spinal cord after experimental infection [111]. Mongolian gerbils could then be useful to study the neurological disorders associated with HEV infection.…”
Section: Animal Models Of Hevmentioning
confidence: 99%
“…Finally, HEV RNA was detected in the liver from seven to 42 days post infection, which is consistent with the last days of HEV RNA detection in the swine model [110], suggesting that HEV RNA replication in the Mongolian gerbil is similar to its replication in the swine model. Using this model, a study has also shown that swine HEV-4 is able to cross the blood–brain barrier and replicate in the brain and the spinal cord after experimental infection [111]. Mongolian gerbils could then be useful to study the neurological disorders associated with HEV infection.…”
Section: Animal Models Of Hevmentioning
confidence: 99%
“…It has been argued that neural damage is immune mediated (supported by reports of delays between infection and neuropathological presentation),14 that it may result from HEV-evoked autoimmunity (substantiated by links between HEV and autoimmune thyroiditis),15 16 and that HEV can act as a neurotropic agent, directly affecting the central nervous system. The latter is supported by evidence that HEV genotype 4 can cross the blood–brain barrier,17 and the discovery of different HEV quasispecies in the serum and cerebrospinal fluid of a kidney transplant patient 18. Regardless of the pathophysiology, a clear temporal link is demonstrated between HEV infection and neurological disease in case reports, such as this one, throughout the literature.…”
Section: Discussionmentioning
confidence: 70%
“…The timing of neurological manifestations after HEV infection has not been well described, but ranged from 12–60 months in 1 review of 6 cases in immunosuppressed patients. In animal models, HEV is able to cross the blood–brain barrier, replicate in the central nervous system, and cause neuronal necrosis and myelin degeneration [10]. …”
Section: Discussionmentioning
confidence: 99%